PROFIL PETERNAK SAPI PERAH DESA KEMIRI KECAMATAN JABUNG KABUPATEN MALANG - Catur Budi Prayitno; Khusnul Khotimah (Jurnal Gamma, 2011)
Catur Budi Prayitno 1 & Khusnul Khotimah21 Mahasiswa & 2Staf Pengajar Jurusan Produksi Ternak, Fakultas Pertanian Peternakan,Universitas Muhammadiyah MalangAlamat Korespondensi : Jln. Terusan Siguragura c/4 MalangEmail: thuthul17@yahoo.comABSTRACTDairy farms in this region are the type of people that still is conventional, with the ownershipof dairy cows and the hereditary possession of the scale of 1-5 tail, only about 2% of the ownershipscale possess more than 5 individuals. The results are expected to use the data for a policy in thedevelopment of dairy cattle in the future to related parties (Department of Animal Husbandry) andwho needs it. The research method used was a survey, by means of direct interviews with respondentsto the questionnaire reference to primary data, and supporting data from relevant agencies (KUBEPSP Forward Steady and Pecan Village Office) as supporting data or secondary data.The results of this study reported that 72% of villagers Pecan livelihood as dairy farmers, 47%of dairy farmers in the village are in the productive age Pecan 26-45 years, but the level of theaverage dairy cow ownership of selected samples only 1-2 tail. Rerta milk production of each parentabout 7.9 liters per day, the quality of the milk produced has memmenuhi ISO standard, the averagefat content of 3.5 and above and protein 2.5 and above, whereas about 11% TS .. The success rateof AI (Artificial Insemination) in the category of fairly good at around 67%. Constraints in dairycattle breeding is limited to the amount of water and forage in the dry season were replaced with theaddition konsntrat and sugarcane shoots, so it becomes a problem in the decline in the quality andmilk production.The conclusion of this is penlitian Pecan Village is a central area of dairy cows in the Jabung,East Malang msih farm business is conventional, but it is the principal source of income is not asideline business, because almost 70% of the population depends perahnya cattle business in meetingsoial economic needs. Suggestions to consider is the need for attention from stakeholders especiallylocal governments, related facilities and infrastructure development related livestock water facilitiesand scale of livestock ownership for farmers to increase the welfare of the people as well as a touchof food technology for continuous availability.